Does Income Matter? Financial Literacy, Financial Health, and Financial Well-Being: PLS-MGA Evidence - Mawadah, Badriatul; Jacelyn; Yulfiswandi (Jurnal Manajemen dan Inovasi (MANOVA), 2026)
Objective – This research aims to examine the direct and indirect effects of financial literacy on financial well-being, with financial health as a mediating variable, while also exploring differences based on income levels Design/methodology/approach – This study uses a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) and Multi-Group Analysis (PLS-MGA) on 270 young adults aged 25–35 years in Blitar City and Blitar Regency, Indonesia. The variables include financial literacy, financial health, financial well-being, and income as a grouping variable. Findings – The results indicate that financial literacy has a significant positive effect on financial well-being, both directly and indirectly through financial health. Financial health plays a significant mediating role, suggesting that good financial conditions strengthen well-being. Multi-group analysis shows no significant income-based differences in the relationships between financial literacy and financial health, and between financial health and financial well-being. However, a significant difference is found in the direct effect of financial literacy on financial well-being, which is stronger among low-income individuals. Research limitations/implications – This study is limited to young adults in Blitar, Indonesia, which may affect generalizability. Future research should include broader regions and additional variables such as financial behavior or psychological factors. Practical implications – The findings emphasize the importance of improving financial literacy, especially for low-income groups, through targeted programs focusing on budgeting, saving, and debt management Originality/value – This study integrates financial health as a mediator and examines income differences using PLS-MGA, highlighting the stronger role of financial literacy among low-income individuals